THE URGENCY OF PSYCHIATRIC THERAPY SANCTION IMPOSITION AGAINST PERPETRATORS OF PEDOPHILIA - Triana Ohoiwutun (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The pedophilia crime can be imprisoned under the Criminal Code (KUHP) and the Child Protection Act of 2014 (UU Perlindungan Anak Tahun 2014); whereas pedophile can be qualifild as the psychiatric disorder in accordance with ICD, DSM and PPDGJ definition. The imposition of measures psychotherapy is able to be integrated and synergized with the imprisonment penalty based on the concept of criminal individualization and double track system. Therefore the penalties againts pedophiles could be effective and efficient penalties not only the perpetrators but also for the society.Key words: pedophilia, criminal sanctions, psychiatric therapy.